THE HISTORIC BACKGROUND OF “LLAIKO VIMA” NEWSPAPER (1945-2012) - Polo, Olieta (European Scientific Journal, ESJ, 2014)
The aim of this paper is to give a general view of the history of “Llaiko Vima” newspaper of the Ethnic Greek Minority in Albania from the year 1945-2012 in which will be mentioned the general characteristics of “Llaiko Vima” newspaper and mainly its purpose, its publishing team, its circulation, its personality and its ideology, the ideological action frame of its correspodents, its economics and circulation.